How Upward Moral Comparison Influences Prosocial Behavioral Intention: Examining the Mediating Role of Guilt and the Moderating Role of Moral Identity - Zhang, Heyun; Chen, Sisi; Wang, Rong; Jiang, Jiang; Xu, Yan; Zhao, Huanhuan (Frontiers in Psychology, 2017)
Although it has been shown that exceptional good deeds exert influences on people’s prosocial behavior and intention, we have known little about how common moral actions in our daily life. The present study aimed to examine how upward moral comparison influenced prosocial behavioral intention as well as to explore the mediating role of guilt and the moderating role of moral identity in the focal relationship. An experimental study was conducted with 162 Chinese undergraduates (103 women, 59 men) randomly assigned to an upward moral comparison condition, an upward competence comparison condition or a control condition. Results indicated that participants in the upward moral comparison condition experienced higher levels of guilt and exhibited stronger motivation to act prosocially, relative to participants in the other two conditions. That is to say, upward moral comparison induces guilty experience, and then increases people’s prosocial behavioral intention. Moreover, we have found that moral identity internalization moderates the upward moral comparison-guilt relationship, and the indirect effect of upward moral comparison on prosocial behavioral intention via guilt. The implications of these findings were discussed.